2012
DOI: 10.1053/j.semnuclmed.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Precision of Radioactivity Quantification in Nuclear Medicine Images

Abstract: The ability to reliably quantify activity in nuclear medicine has a number of increasingly important applications. Dosimetry for targeted therapy treatment planning or for approval of new imaging agents requires accurate estimation of the activity in organs, tumors, or voxels at several imaging time points. Another important application is the use of quantitative metrics derived from images, such as the standard uptake value commonly used in positron emission tomography (PET), to diagnose and follow treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 44 publications
(39 reference statements)
4
58
0
5
Order By: Relevance
“…Zeintl et al [31] used a cylinder uniformly filled with 99m Tc and reported CNF values similar to those obtained by our group using planar scans of point sources [26]. Frey et al [32] suggests that the use of a phantom tomographic acquisition, instead of a planar scan of a small source, is the optimal approach. Lastly, D’Arienzo et al [33] performed tomographic scans of point sources in air and extended phantoms and showed better quantification accuracy for CNF determined from phantom studies than from point sources.…”
Section: Discussionsupporting
confidence: 66%
“…Zeintl et al [31] used a cylinder uniformly filled with 99m Tc and reported CNF values similar to those obtained by our group using planar scans of point sources [26]. Frey et al [32] suggests that the use of a phantom tomographic acquisition, instead of a planar scan of a small source, is the optimal approach. Lastly, D’Arienzo et al [33] performed tomographic scans of point sources in air and extended phantoms and showed better quantification accuracy for CNF determined from phantom studies than from point sources.…”
Section: Discussionsupporting
confidence: 66%
“…40,41 Corrections for clinical factors, including involuntary (e.g., respiration), or voluntary motions, were only recently proposed. 40,42,43 Hence, the more sophisticated methods to correct SPECT counts to activity are not yet in widespread use, as full corrections of physical factors are not always available, and correction to respiratory motion is possible only in few research centers. Moreover, the hybrid SPECT-CT scanners are not available in all centers.…”
Section: Introductionmentioning
confidence: 99%
“…SUVmax may be the most widely used PET parameter due to its easy access with commercial workstations. SUVmax might be most advantageous in small tumors with less dependency on partialvolume effects [5], however, it can be substantially affected by image noise and therefore depend on reconstruction parameters [1]. Although SUVmean might provide a more representative value for the whole tumor, it will vary depending on which voxels are included in ROI [1,9].…”
Section: Pet Parametersmentioning
confidence: 99%
“…To plan targeted therapy or to assess the response of treatment, measurement of tumor size or estimation of radioactivity concentrations in regions of interest (ROI) are essential [1]. However, anatomic size changes often come later and less specific than functional and molecular changes [2].…”
Section: Introductionmentioning
confidence: 99%